Post-esophageal atresia repair double acquired tracheoesophageal fistulas treated successfully by gastric transposition: a case report - Nobuhiro Takahashi; Yasushi Fuchimoto; Teizaburo Mori; Kiyotomo Abe; Yohei Yamada; Goro Koinuma; Tatsuo Kuroda (Surgical Case Reports)
Abstract Background Postoperative recurrence of tracheoesophageal fistula (TEF) is a frequent complication in the repair of esophageal atresia (EA). Based on the recent etiologic classification, a TEF that develops in a different new pathway from the original one is categorized as an acquired TEF. The TEFs that fall into this category have been reported to be refractory and their mechanisms have not been fully understood. Here, we report the complicated case of an acquired TEF derived from mediastinitis after the original TEF repair developed an anastomotic stricture. The TEF contained double fistulas, both towards the right lobe bronchi, and was repaired by gastric transposition through a retrosternal route. Case presentation The patient was diagnosed with Gross C esophageal atresia after birth and underwent tracheoesophageal fistula banding during the neonatal period. He experienced an intractable anastomotic stenosis after surgery which was treated with repeated balloon dilation therapy. By the age of 11 months, he developed a mediastinal abscess that improved with conservative treatment. At 18 months old, a fistula from the esophagus to the right superior lobe bronchus was identified. The patient underwent a right upper lobectomy to resect the fistula. However, at 21 months old, another fistula to the right lower lobe was revealed. An esophageal banding was done to relieve the respiratory symptoms. This was followed by esophagectomy and gastric transposition through the retrosternal route at 26 months old. The patient started rehabilitation and oral intake gradually after surgery. By 3 years after gastric transposition, he could already take blended food orally with the support of small amounts of enteral feeding. Conclusion Cases of TEF derived from severe inflammation have the potential to form a complicated network and lead to recurrence. Surgeons should consider the possibility of multiple tiny fistulas in cases of severe acquired TEF. These may be repaired successfully by gastric transposition through the retrosternal route.